PENGARUH ELEVASI PERMUKAAN AIR TERHADAP PROBABILITAS KELONGSORAN DAN STABILITAS LERENG TIMBUNAN DI OPEN PIT "X" PT BERAU COAL, KALIMANTAN TIMUR - Maulana, Muhamad Arief; Khoirullah, Nur; Ka'bah, Hanifan Cipta Muamar; Dwi Hadian, Mohamad Sapari (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2023)
At the open pit mining, a place is needed for storing overburden material which is commonly referred as a disposal. In some cases, overburden material is stockpiled in void. Overburden material stockpiling activities require good planning. This research was conducted in the open pit "X" Site Sambarata PT. Berau Coal, East Kalimantan. The purpose of this study is to calculate the value of the safety factor of the slope, calculate the probability of failure and to analyze the effect of the water level on the slope stability. This study used the Bishop method with pseudostatic conditions and fully saturated groundwater conditions. From the results of this study it was found that the value of the slope safety factor in the study area ranged from 0.993 to 1.33 and the value of the probability of failure is 17.1 to 35.6%. The value of the factor of safety and the probability of failure is influenced by the geometry of the slope, distributed load, seismic load, and the height of the water level where the higher the water level in the pit, the value of the slope safety factor is higher and the value of the probability of failure is lower.